Wina i wstyd. Analiza lingwistyczna jako prolegomena do nauczania Kościoła katolickiego z zakresu moralności - Długosz-Kurczabowa, Krystyna; Kietliński, Krzysztof (Studia Theologica Varsaviensia, 2017)
Linguistic analysis carried out showed that the guilt and shame are words inherited from proto-language, about the parallel development. Their common trend in the field of semantics was the transition from the concrete to the abstract and the consequent disappearance of meanings specific. It is also blurred the boundary between these words of Polish general and specialized terms in the field of ethics. Both words occupy a permanent place in the Polish language system, as evidenced by numerous relationships of expression, phraseology, antonymic. Linguistic picture of guilt and shame encourages individual attempts to interpret it. The Catholic Church issue of guilt and shame associated with sin and moral disorder. First of all, it draws attention to the sin of disobedience and pride as a source of human guilt and shame and even guilt. We recommend moderation, which is a moral virtue, to achieve harmony allowing internal and avoid guilt and shame.